DRØMME, ÅNDER OG KOGNITION - Willerslev, Rane (Tidsskriftet Antropologi, 2006)
As a child of the Western intellectual tradition, anthropology has tended not to take its informants’ stories about the existence of spiritual beings seriously. Instead, these stories tend to be accounted for by using a terminology drawn from the theories of representation, which take as their premise that we do not have any direct perceptual access to the world, but need to construct it in our minds by means of our language. This article aims at developing a radically different approach to the study of indigenous spiritual knowledge. It draws on insights from the cognitive sciences, which show that concepts can and do exist independently of language and that dreaming shares basic cognitive processes with waking life. It concludes that it is possible that children can develop prototypical concepts about spirits before they develop language. In this case language would not be fundamental for conceptual thought about spiritual beings.